Strategi Sukses untuk Bisnis Pengetikan dan Fotokopi di Era Digital - Misnawati Misnawati; Nirena Ade Christy; Isman Isman; Anwarsani Anwarsani; Yesni Nopy; Nabila Salwa (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This article explores the store labeled "Komputer dan Fotokopi Salwa" as the main object of study. Focusing on market surveys, typing and photocopying industry trends, online marketing strategies, and key success factors in the typing and photocopying business, this research aims to provide in-depth insights into the dynamics of business in the current digital era. Through data analysis including market surveys that record that 70.2% of jobs require computer devices and similar ones, and 39.9% require document duplication and/or binding, this article presents a comprehensive understanding of market needs and preferences. Additionally, with the majority of respondents (79.8%) having access to computers and laptops, but only a small percentage owning a printer (28.7%), this article highlights the challenges and opportunities faced by the typing and photocopying industry. This analysis provides a foundation for effective online marketing strategies and identifies key success factors that can help businesses like "Komputer dan Fotokopi Salwa" to grow and maintain their position in the current competitive market.